Peningkatan Efisiensi Produksi dan Manajemen Operasional di UD. Assas Jaya melalui Implementasi Mesin Pengering Gabah - Rosady, Siti Duratun Nasiqiati; Novitasari, Eli (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve production efficiency and operational management at UD. Assas Jaya through the implementation of a rice drying machine. So far, the rice drying process is still carried out traditionally by relying on sunlight, so it is less efficient, takes a long time, and is highly dependent on weather conditions. To overcome this problem, the Community-Based Research (CBR) method is used by involving business owners, workers, and academic partners in the process of identifying problems, implementing solutions, and evaluating results. The stages of the activity include analysis of initial conditions, training in the use of drying machines, operational assistance, and evaluation of production efficiency. The results of the activity showed a significant increase in drying time, rice quality, and operational cost efficiency. The implementation of this technology proves that a community-based approach can increase the competitiveness of small businesses in the agricultural sector, while supporting food security through optimization of the production process.